2017
DOI: 10.1155/2017/9810194
|View full text |Cite|
|
Sign up to set email alerts
|

Fatal Systemic Vasoconstriction in a Case of Metastatic Small-Intestinal NET

Abstract: An increased release of serotonin secreted by ileal NETs is thought to be the major factor causing the carcinoid syndrome. However, in acutely arising carcinoid crisis also other vasoactive factors may lead to hazardous fluctuations in blood pressure and bronchial constriction. In rare cases, systemic vasoconstriction can be observed, probably caused by catecholamines or similar acting substances. Here, we report a fatal case of fulminant systemic vasoconstriction possibly caused by catecholamines in a patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Correcting dehydration, electrolyte disorders, and hypoproteinemia are especially important, as well as avoiding alcohol, spicy food, and tryptophan rich food. Physical exertion may also exacerbate the symptoms of CS, so it should be avoided in the days prior to the administration of Lu-DOTA-TATE [ 24 , 27 , 31 , 32 , 34 ]. In functional NETs, and specifically if they present CS, the first-line pharmacological treatment are SSAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correcting dehydration, electrolyte disorders, and hypoproteinemia are especially important, as well as avoiding alcohol, spicy food, and tryptophan rich food. Physical exertion may also exacerbate the symptoms of CS, so it should be avoided in the days prior to the administration of Lu-DOTA-TATE [ 24 , 27 , 31 , 32 , 34 ]. In functional NETs, and specifically if they present CS, the first-line pharmacological treatment are SSAs.…”
Section: Discussionmentioning
confidence: 99%
“…Cyproheptadine, a serotonin receptor blocker, can be used in doses of 4 mg/8 h. Telotristat ethyl has been found to reduce serotonin production by inhibiting tryptophan hydroxylase (TPH). It is indicated in combination with SSA therapy in adults with CS diarrhea inadequately controlled by SSA therapy [ 17 , 24 , 29 , 32 ]. Premedication with benzodiazepines and antihistamines can be useful to reduce anxiety before treatment with PRRT, but its administration is controversial, since histamine release may occur, especially with gastric or bronchial carcinoids [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the possible mechanism behind hormonal secretion during Lu-octreotate therapy (tumor lysis vs. discontinuation of short-acting somatostatin analog vs. emotional stress response to hospitalization vs. administration of arginine and lysine), the Authors concluded that hormonal crises should be managed with an infusion of somatostatin analogs i.v., fluids, corticosteroids and correction of electrolyte disturbances. More recently, Stenzel et al came to the same conclusions [45]. Moreover, the Australian group of Tapia Rico et al first proposed a protocol to prevent and manage severe CC and specifically defined which patients would benefit most ("high-risk patients") from premedication to PRRT therapy with corticosteroids and bolus dose of octreotide sc [46].…”
Section: Octreotidementioning
confidence: 99%
“…In the article titled “Fatal Systemic Vasoconstriction in a Case of Metastatic Small-Intestinal NET” [ 1 ], the first and last names of all the authors were reversed. The revised authors' list is shown above and updated in place.…”
mentioning
confidence: 99%